If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(u + 4) = 2u + -34 Reorder the terms: 9(4 + u) = 2u + -34 (4 * 9 + u * 9) = 2u + -34 (36 + 9u) = 2u + -34 Reorder the terms: 36 + 9u = -34 + 2u Solving 36 + 9u = -34 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 36 + 9u + -2u = -34 + 2u + -2u Combine like terms: 9u + -2u = 7u 36 + 7u = -34 + 2u + -2u Combine like terms: 2u + -2u = 0 36 + 7u = -34 + 0 36 + 7u = -34 Add '-36' to each side of the equation. 36 + -36 + 7u = -34 + -36 Combine like terms: 36 + -36 = 0 0 + 7u = -34 + -36 7u = -34 + -36 Combine like terms: -34 + -36 = -70 7u = -70 Divide each side by '7'. u = -10 Simplifying u = -10
| -2x+7x-3=3x-x+6 | | 9(u+4)=2u-4 | | 16x^2+6x+66=0 | | (3x-9)(3x-9)-12=0 | | 5g+2g+2=12 | | x=1x(4x^2*2x) | | -6x-2-3x-1-3x-1=0 | | 3x^2-12x=-14 | | 3x+24=0 | | g-g+8g-3=114 | | x^3-2x^2-11x+10=0 | | x=2+2 | | 11x^2-5x-5=0 | | 20x+6-4x=12.0+6x | | 2x+2+3x-4= | | 2x+2+3x-4=1 | | 6x-7-2(x-5)=-5 | | 6x^2+4x+6=0 | | 3(5-x)-3+6x=42 | | 4g-2=34 | | -5x+3=4x-24 | | x+2=87 | | 2+5x=17-2x | | 6x^2-3=7x | | 8=0.75x | | 15y^2+28y+12=0 | | 18s^2(s+4)=0 | | 5x-2y+z=5 | | 1.3x+1.2y=3.9 | | y^4-20y^2+64=0 | | 4x-(3-x)= | | x-9y=-12 |